Brassinosteroids on the oxidizing and hydrolyzing enzymes of radish plants – A study - Vidya Vardhini, B; Sujatha, E; Seeta Ram Rao, S (Journal of Phytology, 2012)
The effect of 24-epibrassinolide and 28-homobrassinolide on the activities of two oxidizing enzymes (catalase and peroxidase) and two hydrolyzing enzymes (ribonuclease and protease) of radish plants were studied. Both the brassinosteroids stimulated the activity of the oxidizing enzyme, catalase of the radish plants. The activity of the other oxidizing enzyme peroxidase was decreased by the application of 24-epibrassinolide and 28-homobrassinolide. Brassinosteroid-treatment resulted in lowered protease as well as ribonuclease activity.